Ignatian Radicalism: The Influence of Jesuit Spirituality on Dorothy Day - Peters, Benjamin (The catholic historical review, 2017)
While celebrated in U.S. Catholicism, Dorothy Day (1897–1980) is often marginalized in American Catholic scholarship. One of the ways this marginalization has occurred is by depicting the sources of her theological vision—particularly "the retreat" she embraced in the 1940s—as "Jansenist" or "perfectionist." But "the retreat" has also been portrayed in other ways, and this article will examine the argument that its theology is rooted in the Ignatian Spiritual Exercises and a strain of Jesuit spirituality that includes early modern Jesuits such as Louis Lallement, Jean-Joseph Surin, and Jean Pierre de Caussade. Such an alternative understanding not only retrieves "the retreat" from the margins; it also links Day with other kindred spirits in Ignatian spirituality.